A comprehensive study of nano/micro fillers on silicone rubber insulators: Electrical, mechanical, and thermal characterization - Shohab Ahmad; Rizwan Ahmed; Rahisham Abd Rahman; Ameen Ullah; Arshad Jamal; Rizwan Akram (Results in Engineering)
Over the past three decades, high-temperature vulcanized silicone rubber (HTV-SiR) has found widespread use in electrical applications, especially in High Voltage (HV) domain. Silicone rubber in its pure form is not recommended to be used as an insulator. Hence, this study aims to quantify the impact of a hybrid inorganic nanofillers on the electrical, mechanical, thermal, and tracking/erosion resistance properties of HV outdoor insulating composites based on HTV-SiR. The blend documented as SNMC4 (4 % nano-silica and 20 % micro alumina) demonstrated the highest tensile strength in mechanical properties. The improvement is 24.36 % in SNMC4, 22.98 % in SNMC2, 20.22 % in the case of SNMC6, 14.94 % in SNMC8, and 11.49 % in the case of SNMC10. In contrast, the blend defined as SNMC2 (2 % nano-silica and 20 % micro alumina) demonstrated the highest impact strength in unaged and aged blends. The improvement in insulation properties is 29.45 % in the case of SNMC2, 21.64 % in the case of SNMC4, 20.59 % in the case of SNMC6, 20.29 % in the case of SNMC8, and 15.47 % in the case of SNMC10. Out of all the aged and unaged samples, SNMC2 and SNMC4 had the maximum thermal stability of 400 °C, according to thermal gravimetric analysis (TGA) findings. The inclined plane test (IPT) was conducted following the IEC 60587 standard test to assess composite samples' tracking and erosion resistance. In SNMC2 and SNMC4 samples, the lowest leakage current and weight loss were observed.